2021
DOI: 10.1155/2021/2255017
|View full text |Cite
|
Sign up to set email alerts
|

Increased Death of Peripheral Blood Mononuclear Cells after TLR4 Inhibition in Sepsis Is Not via TNF/TNF Receptor-Mediated Apoptotic Pathway

Abstract: Background. Apoptosis is one of the causes of immune depression in sepsis. Pyroptosis also occurs in sepsis. The toll-like receptor (TLR) 4 and receptor for advanced glycation end products (RAGE) have been shown to play important roles in apoptosis and pyroptosis. However, it is still unknown whether TLR4 inhibition decreases apoptosis in sepsis. Methods. Stimulated peripheral blood mononuclear cells (PBMCs) with or without lipopolysaccharides (LPS) and high-mobility group box 1 (HMGB1) were cultured with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Although all three types of cell death have been studies in sepsis, their communication pathways at the molecular level are largely unknown. Moreover, cell death mediated by apoptosis often occurs in heart, kidney, and other organ failures during sepsis ( 6 ) pyroptosis is more commonly associated with lethal sepsis ( 4 , 7 , 8 ). Necroptosis has also been observed in kidney damage resulting from mitochondrial dysfunction in sepsis ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although all three types of cell death have been studies in sepsis, their communication pathways at the molecular level are largely unknown. Moreover, cell death mediated by apoptosis often occurs in heart, kidney, and other organ failures during sepsis ( 6 ) pyroptosis is more commonly associated with lethal sepsis ( 4 , 7 , 8 ). Necroptosis has also been observed in kidney damage resulting from mitochondrial dysfunction in sepsis ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…One prominent aspect of immunosuppression observed in experimental sepsis was lymphocyte apoptosis. This process further contributed to immunosuppression, making the host more vulnerable to invading pathogens [45][46][47]. Sepsis patients often experienced a signi cant decrease in lymphocyte count, which can be attributed to lymphocyte marginalization, increased apoptosis, and cell redistribution [48].…”
Section: Discussionmentioning
confidence: 99%
“…An essential stage in the onset of experimental sepsis has been identified as lymphocyte apoptosis. This process can further induce a state of immunosuppression, which increases host susceptibility to invading pathogens [ 8 , 25 , 26 ]. Meanwhile, several studies reported that peripheral blood lymphocyte count decreased in patients with sepsis, and lymphopenia was associated with poor outcomes [ 10 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%